Effectiveness of the Role of SMS/WhatsApp Reminders, Blood Pressure Self-Monitoring, and Preeclampsia Education on the Early Detection of Gestational Hypertension at Kosambi Clinic, Tangerang, in 2025 - Abela Mayunita; Yana Karunia Hastuti (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Gestational hypertension and preeclampsia are major contributors to maternal and fetal morbidity and mortality. Early detection through routine blood pressure monitoring is often hindered by low adherence to antenatal care (ANC) visits, limited maternal knowledge, and suboptimal self-monitoring practices. Simple technology-based interventions such as SMS/WhatsApp reminders, home blood pressure self-monitoring, and preeclampsia education may improve early detection of gestational hypertension. Objective: To determine the effectiveness of SMS/WhatsApp reminders, blood pressure self-monitoring, and preeclampsia education in improving early detection of gestational hypertension among pregnant women at Kosambi Clinic, Tangerang, in 2025. Methods: This study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 30 pregnant women (gestational age 20–37 weeks) meeting the inclusion criteria were recruited. The intervention (approximately 1 month) consisted of structured SMS/WhatsApp reminders, training and recording of blood pressure self-monitoring, and preeclampsia education. Data were collected using observation sheets, questionnaires, and blood pressure measurements before and after the intervention. Normality was assessed using the Shapiro–Wilk test, and pre–post differences were analyzed with a paired sample t-test at a significance level of ≤0.050.05≤0.05. Results: Prior to the intervention, 53.6% of participants had blood pressure ≥140/90140/90≥140/90 mmHg. After the intervention, most participants had normal blood pressure (86.67%) and the proportion with hypertension decreased to 13.33%. Mean blood pressure decreased from 147.30 to 132.10, and the paired sample t-test indicated a statistically significant difference (p ≤0.050.05≤0.05). Conclusion: The combined intervention of SMS/WhatsApp reminders, blood pressure self-monitoring, and preeclampsia education was effective in supporting early detection and improving blood pressure control among pregnant women, potentially reducing the risk of complications related to gestational hypertension.